1990
DOI: 10.3727/036012990816358252
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Enhanced Effect of Acupuncture Analgesia and Acupuncture Anesthesia by D-Phenylalanine (2nd Report) - Schedule of Administration and Clinical Effects in Low Back Pain and Tooth Extraction

Abstract: D-phenylalanine (DPA) is known to block the activity of carboxypeptidase, an enzyme which degrades enkephalins, endogenous morphine-like substances. Therefore, it is considered that DPA administered as an inhibiting drug of this degrading enzyme might prolong analgesia induced by acupuncture. 1) Thirty patients suffering from chronic low back pain were treated with acupuncture 30 minutes after the oral administration of 4.0 grams of DPA. The results were: excellent in 7 cases, good in 11, fair in 6 and poor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Lack of attenuation of nociceptive stimulation could also be explained by no or delayed release of endogenous opioid agonists. Nonetheless, increased levels of endogenous opioid agonists have been found within 20 min of low‐frequency EA stimulation (14, 15), i.e. the duration of EA or sham procedures chosen in the present and previous (1) studies.…”
Section: Discussionmentioning
confidence: 90%
“…Lack of attenuation of nociceptive stimulation could also be explained by no or delayed release of endogenous opioid agonists. Nonetheless, increased levels of endogenous opioid agonists have been found within 20 min of low‐frequency EA stimulation (14, 15), i.e. the duration of EA or sham procedures chosen in the present and previous (1) studies.…”
Section: Discussionmentioning
confidence: 90%
“…The blood cortisol levels of the horses were significantly increased after 30 minutes of electroacupuncture treatment [13]. The release of endogenous opioids was consistent with acupuncture analgesia [12] and was potentiated by D-phenylalanine, which inhibited enkephalinase-mediated degradation of enkephalins and endorphins [14]. However, the opioid antagonist naloxone was able to reverse the effect of acupuncture analgesia in animals [15].…”
Section: Discussionmentioning
confidence: 93%
“…A neurohumoral mechanism also is supported by studies which demonstrate that human spinal cerebrospinal fluid endorphins and dynorphins increase after AP and during the period of analgesia [26]. This release of endogenous opioids coincides with AP analgesia and can be potentiated by preadministration of D-phenylalanine, which inhibits enkephalinase-mediated degradation of enkephalins and endorphins [27]. Furthermore, several studies have shown that the opioid antagonist naloxone can reverse or antagonize AP analgesia in animals [28] and humans [29].…”
Section: Neuromodulatory Mechanisms Of Ap Analgesiamentioning
confidence: 95%